PENGARUH GAYA KEPEMIMPINAN DAN PROFESIONALITAS KEPALA SEKOLAH TERHADAP BUDAYA SEKOLAH DI SD IT AULIA MUARA BULIAN - siti maisarah (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi, 2023)
This Study aims to determine the influence of the style of leadership on the school culture, the influence of headmaster professionalism of the school culture, The influence of the style of leadership and the headmaster professionalism of the school culture at SD IT AULIA Muara Bulian. This research uses a quantitative approach by determining the sample using survey technique. Data collection techniques were done by distributing questionnaires and documentation. Data analysis techniques include validity test, reliability test, normality test, homogeneity, linearity and path analysis. The result of research shows that shows that the influence of the style of leadership (X1) on the school culture (Y) is 68,7%, The result of headmaster professionalism (X2) of the school culture (Y) is 9,07%, Then the influence of the style of leadership (X1) and the headmaster professionalism (X2) of the school culture (Y) is 64,4%. This shows that the influence of style leadership (X1) and headmaster professionalism (X2) school culture (Y) have a positive effect. Because of the influence of exogenous variables (the style of leadership and headmaster professionalism of the school culture) is almost close to100% only 35,5 % influenced by other variables not investigated in this study.